Peran Mediasi Loyalty Employee dan Green Creativity yang Mempengaruhi GSCM Terhadap Competitive Advantage Pada Alfamart - Endang Sukarya; Noviadi Suryawan; Baenur Sidiq; Ruliyanti Cahyani; Retno Purwani Setyaningrum (Journal of Trends Economics and Accounting Research, 2023)
This study aims to examine the influence of Green Supply Chain Management (GSCM) on Competitive Advantage (CA), considering the mediating role of Loyalty Employee (LE) and Green Creativity (GC) at Alfamart in Kabupaten Bekasi. The Structural Equation Modelling (SEM) method was used to analyze data collected from 50 respondents in the company. The latent variables in this study include GSCM, Loyalty Employee, Green Creativity, and Competitive Advantage. The analysis results show that the research model has a good Goodness of Fit Index (GFI) and Comparative Fit Index (CFI), which are 0.926 and 0.951, respectively. In addition, there is a positive and significant influence of GSCM on Competitive Advantage, which can be mediated by Loyalty Employee and Green Creativity. The analysis results also show that Loyalty Employee and Green Creativity mediate the relationship between GSCM and Competitive Advantage positively and significantly. Therefore, Alfamart in Kabupaten Bekasi can improve its CA by implementing socially and environmentally responsible GSCM, and paying attention to Loyalty Employee and Green Creativity as important mediators in the relationship between GSCM and Competitive Advantage.